Internal Cash Flow, Sales Growth, Firm Size, and Capital Expenditure on Telecomunication Companies at Indonesian Stock Exchange 2017-2021 - Agus Hermawan; Makmuri Ahdi (Faculty of Islamic Economics and Business IAIN Syekh Nurjati Cirebon, 2023)
This research aims to test and analyze the influence of internal cash flow, sales growth, and firm size on the capital expenditure of telecommunication companies at the Indonesian Stock Exchange 2017-2021. The method used in this research is quantitative. The data used is secondary data, namely the financial reports of telecommunications companies, which are the population in this study. The sample used was 14 companies using the purposive sampling method. The analysis method uses panel data regression analysis using the Eviews 12 application. The research results show that internal cash flow has a significant influence on capital expenditure in telecommunications companies listed on the Indonesia Stock Exchange in 2017-2021. The greater the company's internal cash flow, the greater the company's capital expenditure. Sales growth has a significant influence on capital expenditure in telecommunications companies listed on the Indonesia Stock Exchange in 2017-2021. When sales growth increases, network users increase, so an adequate network is needed, and requires capital expenditure to meet network development needs. Firm size does not have a significant influence on capital expenditure in telecommunications companies listed on the Indonesia Stock Exchange in 2017-2021. The larger the company, the greater the capital required for the company's operational activities.